2001
DOI: 10.1046/j.1365-294x.2001.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

rbcL sequences reveal multiple cryptic introductions of the Japanese red alga Polysiphonia harveyi

Abstract: In Europe, the last 20 years have seen a spectacular increase in accidental introductions of marine species, but it has recently been suggested that both the actual number of invaders and their impacts have been seriously underestimated because of the prevalence of sibling species in marine habitats. The red alga Polysiphonia harveyi is regarded as an alien in the British Isles and Atlantic Europe, having appeared in various locations there during the past 170 years. Similar or conspecific populations are know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 31 publications
3
91
1
5
Order By: Relevance
“…The occurrence and impact of such invasions may however be underestimated in cases of cryptic invasions, i.e., when a native species becomes admixed or even genetically replaced by one or multiple distinct genetic lineages of the same species (Saltonstall 2002;Mabuchi et al 2008;Holsbeek et al 2008). Cryptic invasions are commonly unrecognized because the invaders are in many cases mistaken for native species (Saltonstall 2002;Mabuchi et al 2008), yet the invading lineage may differ from their native counterparts in their phenotype (Holsbeek et al 2008;Mackie et al 2012) and/ or physiology (McIvor et al 2001). Such phenotypic changes are however less often reported because relatively few cases exist where historical records are available to document phenotypic changes following a cryptic invasion (Wandeler et al 2007;Crispo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and impact of such invasions may however be underestimated in cases of cryptic invasions, i.e., when a native species becomes admixed or even genetically replaced by one or multiple distinct genetic lineages of the same species (Saltonstall 2002;Mabuchi et al 2008;Holsbeek et al 2008). Cryptic invasions are commonly unrecognized because the invaders are in many cases mistaken for native species (Saltonstall 2002;Mabuchi et al 2008), yet the invading lineage may differ from their native counterparts in their phenotype (Holsbeek et al 2008;Mackie et al 2012) and/ or physiology (McIvor et al 2001). Such phenotypic changes are however less often reported because relatively few cases exist where historical records are available to document phenotypic changes following a cryptic invasion (Wandeler et al 2007;Crispo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2004), Neosiphonia harveyi (McIvor et al. 2001), Gracilaria vermiculophylla (Kim et al. 2010) have suggested that many widespread introductions may have originated from a particularly successful introduced population (corresponding to a restricted number of genotypes) rather than from genotypes representative of the native range (Lombaert et al.…”
Section: Discussionmentioning
confidence: 99%
“…Stuercke & Freshwater, 2010). Likewise, some introduced species of Polysiphonia closely resemble native species and require molecular analyses to identify them reliably (McIvor et al, 2001;Geoffroy et al, 2012). In this regard, numerous introductions of macroalgae to the Atlantic European coasts have been reported over the past four decades (Farnham, 1980;Maggs & Stegenga, 1999;Hewitt et al, 2007;BĂĄrbara et al, 2008;Couceiro et al, 2011;Mineur et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerous introductions of macroalgae to the Atlantic European coasts have been reported over the past four decades (Farnham, 1980;Maggs & Stegenga, 1999;Hewitt et al, 2007;BĂĄrbara et al, 2008;Couceiro et al, 2011;Mineur et al, 2012). Moreover, the actual number of invaders and their impacts may have been seriously underestimated (McIvor et al, 2001). The only species of Polysiphonia sensu lato previously reported as introduced to the Atlantic Europe are Neosiphonia harveyi and P. morrowii from Atlantic North America and Japan, respectively (Maggs & Stegenga, 1999;McIvor et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation